2021
DOI: 10.1080/02701367.2021.1886226
|View full text |Cite
|
Sign up to set email alerts
|

Season-Long Changes in the Body Composition Profiles of Competitive Female Rugby Union Players Assessed via Dual Energy X-Ray Absorptiometry

Abstract: and Russell, Mark (2021) Season-long changes in the body composition profiles of competitive female Rugby Union players assessed via dual energy x-ray absorptiometry. Research Quarterly for Exercise and Sport .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Eight studies, as summarized in Table 3, reported the anthropometric and body composition characteristics of 212 national and international players (age: 26 6 2.4 years, stature: 1.67 6 3.1 m, body mass: 72.4 6 6.3 kg). Two studies reported anthropometric measures by DXA alone (16,60), with 3 studies reporting measures via skinfold (20,22,58), and one study reporting measures by ADP (36). The remaining studies used a combination of DXA and skinfolds (39) and skinfolds and BIA (41), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies, as summarized in Table 3, reported the anthropometric and body composition characteristics of 212 national and international players (age: 26 6 2.4 years, stature: 1.67 6 3.1 m, body mass: 72.4 6 6.3 kg). Two studies reported anthropometric measures by DXA alone (16,60), with 3 studies reporting measures via skinfold (20,22,58), and one study reporting measures by ADP (36). The remaining studies used a combination of DXA and skinfolds (39) and skinfolds and BIA (41), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ensuring the standardization of body composition assessment protocols and data dissemination all need to be considered (43) in future research within women's R15s players. More recently, research investigating DXA-derived body composition indices within women's R15s players has been undertaken (16,39,60). However, there is a lack of longitudinal data to draw any conclusive reference values or congruent changes in DXA-derived body composition indices over time for women's R15s players.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations